EARNING PER SHARE AND DEBT TO EQUITY RATIO ON STOCK RETURN OF INDUSTRIAL SECTOR MANUFACTURE CABLE COMPANIES IN INDONESIA - Unggul Prayoga Ningtyas; Faizal Ridwan Zamzany; Ummu Salma Alazizah (Faculty of Economic and Business, University of Pasundan, 2022)
This study aims to determine and analyze The Effect of Earning Per Share and Debt to Equity Ratio on Stock Return of Industrial sector manufacture cable companies in Indonesia. This research uses a case study method, because the nature and types of data are secondary. This means that the researcher acts as a second party because it is not obtained directly. Secondary data was obtained from the company's financial statements which were downloaded from www.idx.co.id. The results of the studied show that the Earning Per Share (EPS) and Debt to Equity Ratio (DER) variables as the X variable simultaneously affect the Stock Return as the Y variable. The test results of multiple correlation coefficient analysis (R) stated that there was a very strong relationship between the independent variable and the dependent variables. Simultaneous test results show that the Earning Per Sahre (EPS) and Debt to Equity Ratio (DER) variables simultaneously affect Stock Return. These results are shown through f arithmetic 4.982264 > f table (2;27) = 2.08 with a probability value of 0.014398 ​